EFFECT OF CONTAINER TYPES AND POTTING MEDIA ON THE INITIAL GROWTH OF PTEROCARPUS MACROCARPUS SEEDLINGS - Kajornsrichon, Sunanta (วารสารวนศาสตร์ไทย, 2022)
In tropical nurseries it is often difficult to grow seedlings because of soil conditions such as a high pH. This paper reports on an experiment at the ASEAN-Canada Forest Tree Seed Centre in Thailand to identify the most suitable container type and growing medium for producing seedlings of Pterocarpus macrocarpus. Three container types and three medium types were tested, using a 3 x 3 factorial experiment in a Randomized Complete Block design Container types were 6 x 8 inch (1,000 ml/cavity), 6x4 inch (500 ml/cavity), and Hiko box (133 ml/cavity). Media were coconut husk, mixture of topsoil and coconut husk (1:1:1). Results showed that in the nursery stage seedlings grew best in coconut husk. Seedlings grown in the mixture of topsoil and coconut husk grew better than seedlings grown in the mixture of topsoil, sand. and coconut husk. Seedlings grown in bigger container showed better growth. However, after out-planting, seedlings grown in the Hiko box showed the best result, while medium type had no significant effect on seedling growth.